New and little known taxa of neotenic lyropaeine net-winged beetles (Coleoptera: Lycidae) - Kazantsev, Sergey V. (Zootaxa, 2021)
A new genus and five new species of neotenic lyropaeine net-winged beetles, Plycus prosvirovi gen. nov., sp. nov., Platerodrilus (s. str.) brastagicola sp. nov., P. (s. str.) gorbunovi sp. nov., P. (s. str.) kambanganus sp. nov. and P. (Duliticola) berastagiensis sp. nov., are described from Malaysia and Indonesia. Horakiella Bocakova, 2006, syn. nov. is proposed as a junior synonym of Atamania Kazantsev, 2005. Descriptions of little known members of the subfamily, Lybnopaeus avernus (Kazantsev, 1997), Lyropaeus (Lyroneces) orcinus Kazantsev, 1998, Miniduliticola nelsoni Kazantsev, 2002, Platerodrilus (Zhelongia) grootaerti Kazantsev, 2009, P. (Zh.) holynskae Kazantsev, 2009, P. (Duliticola) svetae Kazantsev, 2009, P. (D.) strbai Kazantsev, 2009, Atamania tembeling Kazantsev, 2002 and Sinodulia gressitti Kazantsev, 2002, are complemented with macrophotographs. Lists of Platerodrilus and Atamania species are provided.